SELF REGULATED LEARNING SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR KOSAKATA BAHASA ARAB BAGI MAHASISWA - Rusuly, Usfiyatur (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2017)
This research is designed as a research action performed to improve students' understanding of Arabic vocabularies by taking several actions aimed at improving (1) Students' motivation in practicing self regulated learning, (2) Students' readiness before entering class, and (3) Students' involvement in teaching and learning process. The subject of the research was the first semester female students of C-26 mubtadi' class in the Special Program of Arabic Language Learning. This research is conducted in a dynamic and complementary process consisting of four important cycles, for example: planning, action, observation, and reflection. From the analysis, it is revealed that there were some actions that positively affected the students' understanding of Arabic vocabularies.